2012
DOI: 10.1002/mc.21934
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphisms and haplotypes of WWOX gene are associated with the risk of lung cancer in southern and eastern chinese populations

Abstract: The WW domain-containing oxidoreductase (WWOX) gene is an identified tumor suppressor gene, of which several single nucleotide polymorphisms have been reported to contribute to cancer susceptibility. We hypothesized that genetic variations in WWOX are associated with lung cancer risk. In two independent case-control studies conducted in southern and eastern Chinese, we genotyped five tagSNPs of WWOX gene (rs10220974C > T, rs3764340C > G, rs12918952G > A, rs383362G > T, and rs12828G > A) in 1,559 lung cancer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Several studies have suggested that WWOX polymorphic variants are consistently associated with more aggressive phenotypes and poor outcomes in numerous malignant diseases, including esophageal squamous cell carcinoma, thyroid carcinoma, pancreatic cancer, and lung cancer [36, 4042]. In the current study, we evaluated variations in the WWOX gene and the clinicopathological development of HCC across 2 independent individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that WWOX polymorphic variants are consistently associated with more aggressive phenotypes and poor outcomes in numerous malignant diseases, including esophageal squamous cell carcinoma, thyroid carcinoma, pancreatic cancer, and lung cancer [36, 4042]. In the current study, we evaluated variations in the WWOX gene and the clinicopathological development of HCC across 2 independent individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the selection of 5 well-characterized common polymorphisms from WWOX gene is based on their wide associations with the development of cancer [35, 36]. We included rs11545028 in the 5’UTR region.…”
Section: Methodsmentioning
confidence: 99%
“…Functional annotations from the ENCODE data indicate that rs11545028 is located in the region of an open chromatin, which probably corresponds to the promoters and CpG islands of WWOX . Several studies have documented the importance of transcriptional regulation between WWOX polymorphisms and cancer risk [23, 33]. Moreover, the common modifications of epigenetic changes in chromatin include DNA methylation, which has been considered a crucial mechanism underlying the inactivation of tumor suppressor genes as well as the loss of heterozygosity and mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the selection of 5 well-characterized common polymorphisms from WWOX gene is based on their wide associations with the development of cancer (Table 1, Figure 1A) [2326, 33]. We included rs11545028 in the 5′UTR region.…”
Section: Methodsmentioning
confidence: 99%
“…Th e variants in WWOX also aff ect susceptibility of lung cancer (19). As an oxidoreductase, WWOX contains a short-chain dehydrogenase/reductase domain and participates in pathways involving oxidative stress (20), and thus may play a role in development of COPD, because oxidative stress is a key etiological mechanism of COPD (21).…”
mentioning
confidence: 99%